The effects of medium cut-off and high-flux membranes on activated clotting time of patients on hemodialysis - Lucca, Isabela Pereira; Armani, Rachel; Carvalho, Aluizio B.; Manfredi, Silvia R.; Silva, Monique V. Rocha E.; Gratão, Thamires B.; Silva, Lidia; Watanabe, Renato; Canziani, Maria Eugenia (Frontiers in Nephrology, 2023)
Introduction: The interaction between blood and dialysis membrane increases the risk of clot formation. Membrane properties can interfere with the coagulation activation during dialysis. Heparin is usually used for assuring the anticoagulation, which can be monitored by the Activated Clotting Time (ACT). The purpose of this study was to compare the ACT of patients with chronic kidney disease (CKD) undergoing hemodialysis with high-flux (HF) and medium cut-off (MCO) membranes. Methods: This is a prospective, randomized, crossover study, in which 32 CKD patients were dialyzed for 12 weeks with each membrane. Blood clotting measured by ACT was evaluated at the beginning, 2nd and 4th hour of the dialysis session. Throughout the study, there were no changes in the dose or administration method of heparin. Results: Patients were mostly middle-aged, non-black male, on hemodialysis for 8 years. Before randomization, ACT values were 132±56, 195±60 and 128±32 seconds at pre-heparinization, 2nd and 4th hour, respectively. After 12-week, ACT values in HF and MCO groups were 129±17, 205±65 and 139±38 seconds, and 143±54, 219±68 and 142±45 seconds, respectively. An ANOVA model adjusted and unadjusted for repeated measures showed a significant time, but no treatment or interaction effects. In an additional paired-sample analysis, no difference between ACT values of HF and MCO Groups was observed. Discussion and Conclusion: There was no difference regarding blood clotting during dialysis therapy using HF or MCO membranes. This data suggests that no adjustment in the dose or administration method of heparin is necessary with the use of MCO dialysis membranes.